Acquired Methemoglobinemia- An Overview - Thomas, Shibi Mary; Cherian, Jobin John; Thampi, Syama Priya; George, Blessy (Indian Journal of Pharmacy Practice)
Methemoglobinemia is a life-threatening condition that can be congenital or acquired. It is characterized by the inability of haemoglobin to carry oxygen because the ferrous part of the heme molecule has been oxidized to ferric state. Acquired methemoglobinemia is due to medication or chemicals that cause the rate of methemoglobin formation to exceed its rate of reduction. We performed a search of American National library of Medicine (PubMed) with the following key word “Acquired Methemoglobinemia”. Two hundred forty-two episodes (40.1% published in year 2000 or after) were found. A retrospective case series was found. In which it describes the cases of acquired methemoglobinemia detected and the clinical circumstances under which they occurred at two tertiary care hospitals and affiliated outpatient clinics over 28 months. One hundred thirty-eight cases of acquired methemoglobinemia were detected over 28 months. There were no gender predisposition and performed over a wide range of age (Patient aged 4 days to 86 years). Signs and symptoms of acquired methemoglobinemia usually occur within 20-30 min of drug administration. One of first sign is cyanosis. Early symptoms include anxiousness and dizziness, with fatigue and confusion. The diagnosis of methemoglobinemia is based on clinical assessment when respiratory status does not explain the cyanosis that a patient has and is refractory to oxygen therapy. As management of methemoglobinemia depends on precise detection, clinicians who administer or prescribe oxidizing agent must be aware of clinical symptoms of methemoglobinemia. Methylene blue is currently the drug of choice for the management of methemoglobinemia. Synonyms: Haemoglobin M disease; Erythrocyte reductase deficiency; generalized reductase deficiency, Gibson’s syndrome.
Keywords: Methemoglobinemia; Haemoglobin; Ferrous; Ferric; Oxidation; Acquired Methemoglobinemia; Cyanosis; Anxiousness; Dizziness; Methylene Blue.